2019
DOI: 10.1073/pnas.1903165116
|View full text |Cite|
|
Sign up to set email alerts
|

Treg-mediated prolonged survival of skin allografts without immunosuppression

Abstract: Injection of Interleukin-2 (IL-2) complexed with a particular anti–IL-2 monoclonal antibody (mab) JES6-1 has been shown to selectively expand CD4+Foxp3+ T regulatory T cells (Tregs) in vivo. Although the potency of this approach with regard to transplantation has already been proven in an islet transplantation model, skin graft survival could not be prolonged. Since the latter is relevant to human allograft survival, we sought to improve the efficiency of IL-2 complex (cplx) treatment for skin allograft surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…The main highlight of this study was the early and continued presence of CD4 and CD8 Tregs within the NPSC grafts. CD4 Tregs have been implicated in prolongation of allograft survival and recently have been demonstrated to improve survival of xenografts 20 24 , 40 . Tregs have been shown to mediate immune tolerance and homeostasis by suppressing T effector cells, inhibiting cell–cell contact with APCs, and secreting regulatory cytokines 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The main highlight of this study was the early and continued presence of CD4 and CD8 Tregs within the NPSC grafts. CD4 Tregs have been implicated in prolongation of allograft survival and recently have been demonstrated to improve survival of xenografts 20 24 , 40 . Tregs have been shown to mediate immune tolerance and homeostasis by suppressing T effector cells, inhibiting cell–cell contact with APCs, and secreting regulatory cytokines 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that blocking IL-6 production and IL-6 signaling in combination with co-stimulatory blockade inhibited Th1 responses, and promoted transplant tolerance (Zhao et al, 2012). Recently, the role of IL-6 in allograft rejection was revisited (Pilat et al, 2019). These authors showed that in combination with rapamycin and an anti-IL-2 monoclonal antibody plus IL-2-complex, blocking IL-6 prolonged MHC mismatched skin transplants for greater than 75 days (Pilat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of IL-6 in allograft rejection was revisited (Pilat et al, 2019). These authors showed that in combination with rapamycin and an anti-IL-2 monoclonal antibody plus IL-2-complex, blocking IL-6 prolonged MHC mismatched skin transplants for greater than 75 days (Pilat et al, 2019). Here, we show that T cell derived IL-6 production was inhibited in the presence of Treg EVs, suggesting one way that these vesicles may have abrogate T cell alloresponses seen in our mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite prolonging the survival of islet allografts, IL-2 mab complexes failed to augment the survival of skin allografts as monotherapy ( 53 ). However, later experiments showed that modification of the treatment protocol led to prolonged skin allograft survival.…”
Section: Treg Expansion In Vivomentioning
confidence: 99%